Assessment of Dental Anxiety Levels among the University Teaching Faculty from different Fields of Medicine and Healthcare - Wali, Aisha; Siddiqui, Talha M; Hashmi, Sidra Tul Muntaha; Hassan, Sherbano; Karim, Hashmat (Journal of Orofacial Research, 2014)
Dental anxiety is considered to be a multidimensional fear that can be acquired by a number of parameters involving both personality and psychological traits as well as conditioning experiences and vicarious learning from role models. A cluster sampling technique was used for the study purpose. The sample population included faculty members of Baqai Medical University related to different fields of medicine and healthcare. Data were analyzed by SPSS version 19. Chi-square test was done to compare association of dental anxiety with different fields of medicine and healthcare. Group comparisons were done by using one-way ANOVA test and post hoc Tukey’s test